2015
DOI: 10.1038/ncomms9615
|View full text |Cite
|
Sign up to set email alerts
|

Formation of functional super-helical assemblies by constrained single heptad repeat

Abstract: Inspired by the key role of super-helical motifs in molecular self-organization, several tandem heptad repeat peptides were used as building blocks to form well-ordered supramolecular nano-assemblies. However, the need for stable helical structures limits the length of the smallest described units to three heptad repeats. Here we describe the first-ever self-assembling single heptad repeat module, based on the ability of the non-coded α-aminoisobutyric acid to stabilize very short peptides in helical conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
111
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 50 publications
6
111
1
Order By: Relevance
“…Recently, we reported the solution state morphology and solid-state structure of the peptide SHR-FF (H 2 N-Ser-Aib-Phe-Ser-Aib-Phe-Aib-OH; Fig. 1a), containing α-aminoisobutyric acid residues (Aib)26. We observed that all the amino acid residues, except phenylalanine (Phe), adopted dihedral angles in accordance with a Ramachandran plot of a 3 10 helix26.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Recently, we reported the solution state morphology and solid-state structure of the peptide SHR-FF (H 2 N-Ser-Aib-Phe-Ser-Aib-Phe-Aib-OH; Fig. 1a), containing α-aminoisobutyric acid residues (Aib)26. We observed that all the amino acid residues, except phenylalanine (Phe), adopted dihedral angles in accordance with a Ramachandran plot of a 3 10 helix26.…”
Section: Resultsmentioning
confidence: 61%
“…1a), containing α-aminoisobutyric acid residues (Aib)26. We observed that all the amino acid residues, except phenylalanine (Phe), adopted dihedral angles in accordance with a Ramachandran plot of a 3 10 helix26. The discrepancy in dihedral angles of Phe prompted us to refine the original design by modifying SHR-FF.…”
Section: Resultsmentioning
confidence: 94%
“…[20] On the contrary,n oi ntramolecular interactions exist in the neutral Fmoc-FF.Next, we studied the molecular mechanism underlying the distinctive self-assembly behaviors of Fmoc-FF with different charged states using all-atom molecular dynamics (AAMD) simulations. [20] On the contrary,n oi ntramolecular interactions exist in the neutral Fmoc-FF.Next, we studied the molecular mechanism underlying the distinctive self-assembly behaviors of Fmoc-FF with different charged states using all-atom molecular dynamics (AAMD) simulations.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Zuschriften formation of helical structures. [20] On the contrary,n oi ntramolecular interactions exist in the neutral Fmoc-FF.Next, we studied the molecular mechanism underlying the distinctive self-assembly behaviors of Fmoc-FF with different charged states using all-atom molecular dynamics (AAMD) simulations. [21] After 50 ns AAMD simulations,itis obvious that the Fmoc-FF nanofibril almost keep the antiparallel b-sheet conformation, indicating such as econdary structure is energetically favorable for the Fmoc-FF assemblies with lowcharged state.I ns harp contrast, the starting model for the negatively charged Fmoc-FF À becomes quickly unstable and undergoes as tructural transition from ap arallel b-sheet to ahelix-featured morphology (Figure 3c and d).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[2][3][4][5][6] Tr ansfer of chirality can takes place from 1) single molecules to one-dimensional (1D) assemblies and then from 2) 1D helical assemblies to macroscopic superstructures.I np rinciple,e ach step in this propagation process can determine the overall supramolecular chirality of the system and therefore sometimes creates ambiguity in predicting the handedness of helical assemblies. [2][3][4][5][6] Tr ansfer of chirality can takes place from 1) single molecules to one-dimensional (1D) assemblies and then from 2) 1D helical assemblies to macroscopic superstructures.I np rinciple,e ach step in this propagation process can determine the overall supramolecular chirality of the system and therefore sometimes creates ambiguity in predicting the handedness of helical assemblies.…”
mentioning
confidence: 99%